Peran Corporate Social Responsibility Memediasi Pengaruh Penerapan Green Accounting dan Kinerja Lingkungan Terhadap Profitabilitas Perusahaan yang Terdaftar di Bei - I Wayan Renold Tino; I Putu Sudana (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
The profitability of a company, as reflected by ratios such as Return on Assets (ROA), measures its ability to generate profit from operational activities. In the consumer non-cyclical sector, while some companies have experienced a decline in profits, financial performance tends to remain stable. This study employs purposive sampling to obtain 106 observations and panel data regression analysis to explore the impact of green accounting, environmental performance, and CSR on profitability, given the varying results from previous studies. The research findings indicate that: 1) Green accounting has a positive effect on corporate social responsibility. 2) Environmental performance does not affect corporate social responsibility. 3) Green accounting does not impact company profitability. 4) Environmental performance does not impact company profitability. 5) Corporate social responsibility affects company profitability. 6) Corporate social responsibility mediates the relationship between green accounting and company profitability. 7) Corporate social responsibility does not mediate the relationship between environmental performance and company profitability.